Induction of apoptosis in RKO colon cancer cell line by an aqueous extract of millingtonia hortensis - Siwapong Tansuwanwong (2018)
Millingtonia hortensis is an important medicinal plant in Southeast Asia, used for the treatment of asthma, sinusitis and as a cholagogue and tonic. The aim of this study was to compare the effects of aqueous and ethanol extracts of Millingtonia hortensis on the induction of apoptosis in an RKO human colon cancer cell line. Viability of RKO cells was assessed by MTT reduction assay. The aqueous extract, but not the ethanol extract of M. hortensis inhibited cell growth and proliferation in a dose- and time-dependent manner. Apoptotic cells were determined by flow cytometry and DNA fragmentation assay. Apoptotic cell numbers increased in a dose-dependent manner after treatment with aqueous extract. DNA ladders were clearly observed in RKO cells treated with 200, 300 and 400 μg/ml of the aqueous extract of M. hortensis for 48 h. These results indicate that the aqueous extract of M. hortensis inhibited cell proliferation in an RKO colon cancer cell line via the apoptosis pathway.